2007
DOI: 10.1103/physrevb.75.195307
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Hall effect of metallicBeSipairδ-doped GaAs structures

Abstract: Metallic samples of Be and Si pair ␦-doped GaAs structures which undergo a metal-insulator transition with a decrease in the hole concentration are investigated by Hall resistance and magnetoresistance measurements. The anomalous Hall effect and negative magnetoresistance are observed from the samples in a temperature range above 70 K. Magnitudes of negative magnetoresistance and anomalous Hall resistance significantly vary among the samples, although their doping conditions are close to one another. Dependenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 30 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…The nonlinearity of the Hall voltage for sample 5 is significantly greater than that for other samples grown under higher As fluxes. 3 Figure 3͑b͒ shows the longitudinal resistance of sample 5 as a function of the applied magnetic field B. The magnetic field was applied in the direction parallel to the current.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The nonlinearity of the Hall voltage for sample 5 is significantly greater than that for other samples grown under higher As fluxes. 3 Figure 3͑b͒ shows the longitudinal resistance of sample 5 as a function of the applied magnetic field B. The magnetic field was applied in the direction parallel to the current.…”
Section: Resultsmentioning
confidence: 99%
“…By utilizing these techniques, different approaches can be used for incorporating the spin degree of freedom into semiconductors. In a recent study, 3 we observed a Hall resistance which has a nonlinear dependence on the applied magnetic field from Be/ Si pair ␦-doped GaAs structures grown by molecular-beam epitaxy ͑MBE͒. In the pair ␦-doped GaAs structures which exhibit p-type conduction, a metalinsulator transition occurs as a result of the strong localization of holes in the ␦-doped layers.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…One is the structure similar to those used in our pervious studies [6], in while a buffer layer was grown under different As fluxes to different thicknesses at 580 ℃ as shown in Fig. 1(a).…”
Section: Methodsmentioning
confidence: 99%
“…We also found that the samples exhibiting negative magnetoresistance gave rise to the Hall resistance which has nonlinear dependence on the applied magnetic field. Because of their close correlation, the nonlinear Hall resistance and negative magnetoresistance were explained as a result of localized spins in delta-doped layers [6]; they are explained as the anomalous Hall effect(AHE) and reduced spin-disorder scattering, respectively.…”
Section: Introductionmentioning
confidence: 99%